Factors associated with dengue hemorrhagic fever prevention practices: A cross-sectional study - Toto Harto; Roni Ferdi; Desta Rahmawati (School of Health Sciences Al-Ma'arif, 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains an important public health problem in tropical regions, including Indonesia. Community prevention practices are essential because dengue transmission is closely related to household behavior, mosquito breeding sites, and routine vector control activities. This study examined knowledge, attitude, and selected environmental factors as determinants of DHF prevention practices in Laya Village. Methods: This study used a quantitative analytic design with a cross-sectional approach. The population consisted of 359 households in Laya Village. A total of 78 respondents were selected using the Slovin formula and proportional allocation across five neighborhood clusters. Data were collected using structured questionnaires measuring knowledge, attitude, environmental factors, and DHF prevention practices. Environmental factors included the presence of discarded items, the habit of hanging clothes, and the use of mosquito repellents. Data were analyzed using univariate analysis and the Chi-square test. Results: Most respondents had good knowledge (61.5%), good attitudes (52.6%), good management of discarded items (76.9%), good practice regarding hanging clothes (56.4%), and good use of mosquito repellents (83.3%). However, DHF prevention practices were mostly categorized as poor (51.3%), followed by adequate (42.3%) and good (6.4%). Bivariate analysis showed a significant relationship between knowledge and DHF prevention practices (p = 0.008). Attitude (p = 0.065), presence of discarded items (p = 0.119), habit of hanging clothes (p = 0.546), and use of mosquito repellents (p = 0.304) were not significantly associated with DHF prevention practices. Conclusion: Knowledge was significantly associated with DHF prevention practices, while attitude and the three environmental indicators were not significantly associated. Continuous health education, community empowerment, and routine mosquito breeding site control are needed to strengthen DHF prevention at the household and community levels.